The electroencephalogram in a group of normal subjects - Querol L., Mariano (1956)
Were examined 56 normal subjects, with an average age of 21,268 years. Of these, 19 were born in the sea, in the mountains 30 and 7 on the mountain. In the present communication it is only the results of electroencephalographic examination. The criteria for the classification of the results of the electroencephalogram (EEG) are described into four types; the overall results were: 60.7% normal EEGs; electroencephalograms dysrhythmic 25.0%; electroencephalograms limits 5.4%; abnormal electroencephalograms 8.9%. It is emphasized here that the EEG classified as dysrhythmic be considered as normal special reactivity; electroencephalograms limits are questionably abnormal; Finally, it is noted that when speaking of abnormal EEG that is not to say pathological EEG. The 33.9% of those tested did not show slow waves during hyperventilation. Of this group 10.5% were coastal, mountain were 73.7% and 15.3% were born in the mountain (Forest). According to the birthplace, the mountain group showed 46.7% of subjects without slow waves, between the coastal Only 10.5% had no slow waves. Subdividing the subjects for their place of birth and age subgroups shows that the percentage of subjects without slow waves increases with age; within the same age subgroup the percentage of serrano without EEG slow waves during hyperventilation remains lower than coastal. Production mechanisms and control of slow waves in the EEG during hyperventilation are discussed briefly. The largest percentage of mountain without slow waves in the EEG during hyperventilation could be explained by a vagal predominance hiperanfotonía described in these subjects. This statement is a working hypothesis, experimental basis, it will be necessary to verify or refute continuing in a larger number of research subjects of the problems it entails.